Insulating film
By extruding and treating polyamide-based compositions, an insulating film with excellent dielectric strength, high volume resistivity and excellent flame retardant properties is prepared, solving the cost and performance of existing insulating materials, achieving a combination of high performance and low cost.
Patent Information
- Application Number
- CN202380067921.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-23
- Filing Date
- 2023-09-11
- Publication Date
- 2025-05-02
AI Technical Summary
Existing insulating materials have shortcomings in terms of cost and performance, especially in terms of thickness, flame retardancy, dielectric strength, high volume resistivity and cost, which are difficult to meet practical application requirements.
By extruding a polyamide-based composition, performing stretching, thermal fixing and cooling procedures, an insulating film with excellent dielectric strength, high volume resistivity and excellent flame retardant properties were prepared. The composition contains 69% to 89.9% polyamide, 10% to 25% flame retardant, 0.1% to 1.0% acid scavenger and 0% to 5% other additives.
The dielectric strength exceeds 40KV/mm at room temperature, has excellent flame retardant performance, can maintain high dielectric strength stability at high temperatures, and reduce production costs.
Smart Images

Figure BDA0005322643760000121 
Figure BDA0005322643760000142 
Figure BDA0005322643760000143
Abstract
Description
Technical Field
[0001] The present invention relates to a novel use of a polyamide-based composition, and an insulating film prepared from the polyamide-based composition with excellent dielectric strength, high volume resistivity and outstanding flame retardant properties. The insulating film can be used in various technical fields, in particular, in electrical and electronic systems, new energy vehicles, electrical insulating materials for motors (including coil skeletons of insulating films), insulating sheaths, and heat-resistant parts or components. Background Art
[0002] Electric motors or motor generators are necessary for electric vehicles or hybrid cars. For motor applications, insulation and heat resistance are highly demanding properties for devices like winding insulation of motors, electrical coils, wires and cables, and as capacitor dielectrics, which require products in the form of films or papers. The materials used to make such devices should be strong enough to ensure safety with respect to insulation. Such films are usually made of synthetic resins.
[0003] JPH11341714A discloses a motor stator having a cover made of polyphenylene sulfide and glass fiber. The thickness of the cover cannot meet the thickness requirement of the insulating sheet.
[0004] JP 2008-263704 discloses an insulating paper material including heat-resistant sheets made of aramid fibers and located on both sides of the insulating paper material. An adhesive is used to connect the insulating paper material and a resin molded body.
[0005] WO 2015033696 discloses a motor frame, in which an insulating sheet is impregnated with a resin molded body without using an adhesive. The surface of the insulating sheet is made of aramid paper, which is made of aramid fibrids and aramid short fibers. Aramid insulation paper is made of chopped fibers or precipitated fibers through a wet papermaking process and formed by a hot pressing process, which is a good solution due to high melting temperature, excellent heat resistance and insulation performance, inherent flame retardant properties and excellent chemical resistance.
[0006] However, aramid insulation paper is quite expensive. Improvements have been developed to save costs and reduce the sacrifice of properties caused by the use of impregnation or lamination. An example is a composite material of a polymer film and a polymer fiber, such as a polyester film and a polyester fiber, a polyester film and a polyaramid fiber, a polyimide film and a polyaramid fiber, etc. The composite material has the comprehensive characteristics of a film material and a fiber material, significantly improves the tear resistance and impregnation of the insulating material, has better performance than a single material, and is easy to use. However, the cost of the composite material is still at a high level.
[0007] Polyester films (such as polyethylene terephthalate films) are widely used in various industrial applications. However, the heat resistance and dimensional stability of polyester films cannot meet the requirements of practical industrial use.
[0008] JP2000186141A discloses a semi-aromatic polyamide sheet. However, a large number of fisheyes are generated during the manufacturing process. JP2018135414A also discloses a semi-aromatic polyamide sheet containing a black pigment for laser welding. However, it cannot be used as an insulating film either.
[0009] These improvements are still not satisfactory for practical applications, and an insulating film with low thickness, good flame retardancy, strong dielectric strength, high volume resistivity, and low cost is required. Summary of the invention
[0010] The object of the present invention is to provide a novel use of a polyamide-based composition for the preparation of insulating films.
[0011] The inventors have surprisingly found that an insulating film having a dielectric strength of at least more than 40 KV / mm at room temperature can be achieved by extruding a polyamide-based composition followed by a stretching, heat-setting and cooling procedure. The polyamide-based composition comprises:
[0012] A) 69 to 89.9% by weight of polyamide,
[0013] B) 10 to 25% by weight of a flame retardant,
[0014] C) 0.1 to 1.0% by weight of an acid scavenger,
[0015] D) 0 to 5% by weight of further additives,
[0016] The total percentage by weight of components A) to D) is 100%.
[0017] Another object of the present invention is to provide an insulating film which exhibits excellent dielectric strength, high volume resistivity, and outstanding flame retardancy.
[0018] The insulating film of the present invention exhibits excellent flame retardancy, which is close to V-0UL94 VTM for a sample having a thickness of 0.20 mm and close to V-0UL94 for a sample having a thickness of 0.8 mm.
[0019] For the specimens with thicknesses of 0.75 mm and 1.5 mm, the insulating film in the present invention can pass the GWFI (Glow Wire Flammability Index) test at 960° C. according to DIN EN 60695-2-12.
[0020] The insulating film of the present invention has a dielectric strength of more than 40 KV / mm measured in Midel 7131 ester liquid according to IEC 60243-1 at room temperature in a conditioned state.
[0021] The insulating film of the present invention has a dielectric strength exceeding 70 KV / mm measured in Midel 7131 ester liquid according to IEC 60243-1 at room temperature in a dry state.
[0022] The insulating film in the present invention has a dielectric strength exceeding 40 KV / mm measured in Midel 7131 ester liquid according to IEC 60243-1 at 150° C. in a dry state.
[0023] The insulating film of the present invention has a dielectric strength drop of not more than 40%, preferably 35%, at 120°C compared to the dielectric strength at room temperature measured in dry state according to IEC 60243-1 in Midel 7131 ester liquid.
[0024] The insulating film of the present invention has a dielectric strength drop of not more than 45%, preferably 37%, at 150°C compared to the dielectric strength at room temperature measured in dry state according to IEC 60243-1 in Midel 7131 ester liquid.
[0025] Yet another object of the present invention is to provide the use of the insulating film, in particular for producing components in electrical and electronic systems, new electric vehicles, and electrical insulating parts (such as coil bobbins) for motors. DETAILED DESCRIPTION
[0026] Unless otherwise defined, all technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the invention belongs. The above basic definitions or elaborations given in a general sense or within a preferred range apply to the final product and, correspondingly, to the starting materials and intermediates. These basic definitions can be combined with each other as required, i.e., including combinations of general definitions and / or respective preferred ranges and / or embodiments.
[0027] All embodiments and preferred embodiments disclosed herein may be combined as needed, which are also considered to be within the scope of the present invention.
[0028] The terms "a / an" and "the" are used interchangeably with the term "at least one". The phrases "at least one" and "comprising at least one" followed by a list refer to any one of the items in the list and any combination of two or more items in the list. Unless otherwise stated, all numerical ranges include their endpoints and non-integer values between the endpoints.
[0029] The term "about" refers to a range of numbers that one of ordinary skill in the art would consider equivalent to the stated value while achieving the same function or result.
[0030] Unless otherwise indicated, all percentages (%) are "percentages by weight".
[0031] Unless otherwise stated, the term "unit" refers to the repeating units constituting the polyamide.
[0032] As used herein, the term "PA" refers to polyamide. The term "PA* / PA**" refers to a copolymer of PA* and PA**.
[0033] Disclosed is an insulating film comprising:
[0034] A) 69 to 89.9% by weight of polyamide,
[0035] B) 10 to 25% by weight of a flame retardant,
[0036] C) 0.1 to 1.0% by weight of an acid scavenger,
[0037] D) 0 to 5% by weight of further additives,
[0038] The total percentage by weight of components A) to D) is 100%.
[0039] In a preferred embodiment, the insulating film comprises:
[0040] A) 72 to 78.7% by weight of polyamide,
[0041] B) 19.85% to 23% by weight of a flame retardant,
[0042] C) 0.15 to 0.4% by weight of an acid scavenger,
[0043] D) 1.3 to 4.6% by weight of further additives,
[0044] The total percentage by weight of components A) to D) is 100%.
[0045] Preferably, the polyamide is chosen from at least one semicrystalline semiaromatic polyamide having crystalline domains as evidenced by the presence of a melting peak with a melting enthalpy of at least 5 J / g, measured by differential scanning calorimetry (DSC) according to ISO 11357 at a heating rate of 10 K / min.
[0046] The semi-crystalline semi-aromatic polyamide in the present invention comprises dicarboxylic acid units, diamine units and optionally units derived from other monomers such as amino acid and / or lactam units, wherein the dicarboxylic acid units or diamine units have aromatic groups. For example, the semi-aromatic polyamide comprises aromatic dicarboxylic acid units and aliphatic diamine units, or aliphatic and / or alicyclic dicarboxylic acid units and aromatic diamine units.
[0047] The aromatic dicarboxylic acid units may typically be derived from aromatic dicarboxylic acids. The aliphatic dicarboxylic acid units may typically be derived from aliphatic dicarboxylic acids and / or aliphatic dicarboxylic acid chlorides. The alicyclic dicarboxylic acid units may typically be derived from alicyclic dicarboxylic acids and / or alicyclic dicarboxylic acid chlorides.
[0048] The aliphatic or aromatic diamine units may typically be derived from an aliphatic diamine or an aromatic diamine, respectively.
[0049] The amount of these other monomers is preferably 0 to 20 mol%, preferably 0 to 15 mol%, more preferably 0 to 10 mol%, based on the total units constituting the semicrystalline semiaromatic polyamide.
[0050] The aromatic dicarboxylic acid in the present invention preferably contains 8 to 20 carbon atoms, more preferably 8 to 14 carbon atoms, such as terephthalic acid, isophthalic acid, naphthalene dicarboxylic acid and / or biphenyl dicarboxylic acid, more preferably terephthalic acid, naphthalene dicarboxylic acid, a mixture of terephthalic acid and isophthalic acid, and a mixture of terephthalic acid and naphthalene dicarboxylic acid.
[0051] The aliphatic dicarboxylic acids in the present invention preferably contain 4 to 36 carbon atoms, more preferably 5 to 36 carbon atoms, most preferably 5 to 20 carbon atoms or 36 carbon atoms, such as 5, 6, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 and / or 36 carbon atoms. Examples of aliphatic dicarboxylic acids are succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanoic acid, hexadecanedioic acid, octadecanedioic acid, dimer acids having 36 carbon atoms and mixtures thereof, more preferably adipic acid, azelaic acid, sebacic acid, dodecanedioic acid and mixtures thereof.
[0052] The aliphatic dicarboxylic acid chlorides in the present invention preferably contain 9 to 36 carbon atoms, more preferably 9 to 20 carbon atoms, more preferably 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 carbon atoms. Examples of aliphatic dicarboxylic acid chlorides are azelaic acid chloride, sebacoyl chloride, undecanoyl chloride and mixtures thereof.
[0053] The alicyclic dicarboxylic acid in the present invention preferably contains 4 to 20 carbon numbers, more preferably 8 to 20 carbon numbers, more preferably contains a carbon backbone selected from the group consisting of cyclohexane, cyclopentane, cyclohexylmethane, dicyclohexylmethane, bis(methylcyclohexyl) and mixtures thereof, and most preferably selected from the group consisting of cis- and trans-cyclopentane-1,3-dicarboxylic acid, cis- and trans-cyclopentane-1,4-dicarboxylic acid, cis- and trans-cyclohexane-1,2-dicarboxylic acid, cis- and trans-cyclohexane-1,3-dicarboxylic acid, cis- and trans-cyclohexane-1,4-dicarboxylic acid and mixtures thereof.
[0054] The aliphatic diamine in the present invention may be a linear aliphatic diamine or a branched aliphatic diamine, preferably a linear aliphatic diamine. The aliphatic diamine preferably contains 4 to 36 carbon atoms, more preferably 4 to 22 carbon atoms or 36 carbon atoms, and most preferably 4 to 14 carbon atoms, such as 4, 5, 6, 8, 9, 10, 11, 12, 13 and 14 carbon atoms. Examples of linear aliphatic diamines are 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,13-tridecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, 1,20-eicosanediamine, 1,2 2-docosanediamine and mixtures thereof, preferably 1,6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine and mixtures thereof, more preferably 6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine and mixtures thereof. Examples of branched aliphatic diamines are 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, 2,4,4-trimethylhexamethylenediamine, 2,2,4-trimethylhexamethylenediamine, 2,4-dimethyloctanediamine and mixtures thereof, preferably 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2-methyl-1,8-octanediamine, 2,4,4-trimethylhexamethylenediamine, 2,2,4-trimethylhexamethylenediamine and mixtures thereof.
[0055] The aromatic diamine in the present invention is preferably selected from the group consisting of meta-xylene diamine (MXD), para-xylene diamine (PXD), bis(4-aminophenyl)methane, 3-methylbenzidine, 2,2-bis(4-aminophenyl)propane, 1,1-bis(4-aminophenyl)cyclohexane, 1,2-diaminobenzene, 1,3-diaminobenzene, 1,4-diaminobenzene, 1,2-diaminonaphthalene, 1,3-diaminonaphthalene, 1,4-diaminonaphthalene, 2,3-diaminotoluene, N,N'-dimethyl-4,4'-biphenyl diamine, bis(4-methylaminophenyl)methane, 2,2'-bis(4-methylaminophenyl)propane and mixtures thereof, more preferably MXD and / or PXD.
[0056] Suitable amino acids in the present invention preferably contain 4 to 20 carbon atoms, more preferably 4 to 14 carbon atoms, such as 9, 10, 11, 12 or 13 carbon atoms. Examples of amino acids are 4-aminobutyric acid, 6-aminohexanoic acid, 7-aminoheptanoic acid, 8-aminooctanoic acid, 9-aminononanoic acid, 10-aminodecanoic acid, 11-aminoundecanoic acid, 12-aminododecanoic acid and mixtures thereof.
[0057] Suitable lactams in the present invention preferably contain 4 to 12 carbon atoms, more preferably 5 to 12 carbon atoms. Examples of lactams are 2-pyrrolidone (γ-butyrolactam), 2-piperidone (δ-valerolactam), ε-caprolactam, capryllactam, decanolactam, undecanolactam, enantholactam and / or laurolactam, preferably ε-caprolactam and / or undecanolactam.
[0058] In a preferred embodiment of the present invention, the semicrystalline semiaromatic polyamide comprises dicarboxylic acid units and diamine units, and 0 to 20 mol % of units derived from amino acids and / or lactams, based on the total moles of units constituting the semicrystalline semiaromatic polyamide;
[0059] i. wherein the dicarboxylic acid unit is derived from an aromatic dicarboxylic acid (a-1), or a combination of an aromatic dicarboxylic acid (a-1) and other dicarboxylic acids (a-2) including an aliphatic dicarboxylic acid (a-3) and / or an alicyclic dicarboxylic acid. The amount of the aromatic dicarboxylic acid (a-1) is preferably 60-100 mol%, and the amount of the other dicarboxylic acid (a-2) is preferably 0-40 mol%, based on the total moles of the dicarboxylic acid units constituting the semicrystalline semiaromatic polyamide;
[0060] The diamine unit is derived from an aliphatic diamine (b-1), or a combination of an aliphatic diamine (b-1) and an aromatic diamine (b-2). The amount of the aliphatic diamine (b-1) is preferably 80 to 100 mol%, and the amount of the aromatic diamine (b-2) is preferably 0 to 20 mol%, based on the total moles of the diamine units constituting the semicrystalline semiaromatic polyamide; or
[0061] ii. wherein the dicarboxylic acid unit is derived from an aliphatic dicarboxylic acid (a-3) or a combination of an aliphatic dicarboxylic acid (a-3) and an alicyclic dicarboxylic acid. The amount of the aliphatic dicarboxylic acid (a-3) is preferably 80-100 mol%, and the amount of the alicyclic dicarboxylic acid is preferably 0-20 mol%, based on the total moles of the dicarboxylic acid units constituting the semicrystalline semiaromatic polyamide;
[0062] The diamine units are derived from an aromatic diamine (b-2) or a combination of an aromatic diamine (b-2) and an aliphatic diamine (b-1). The amount of the aromatic diamine (b-2) is preferably 80 to 100 mol%, and the amount of the aliphatic diamine (b-1) is preferably 0 to 20 mol%, based on the total moles of the diamine units constituting the semicrystalline semiaromatic polyamide.
[0063] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide comprises dicarboxylic acid units and diamine units, wherein the dicarboxylic acid units are derived from aromatic dicarboxylic acids (a-1), or a combination of aromatic dicarboxylic acids (a-1) and other dicarboxylic acids (a-2) including aliphatic dicarboxylic acids (a-3) and / or alicyclic dicarboxylic acids. The aromatic dicarboxylic acid (a-1) is terephthalic acid, naphthalene dicarboxylic acid, biphenyl dicarboxylic acid, a combination of terephthalic acid and isophthalic acid, or a combination of terephthalic acid and naphthalene dicarboxylic acid; the amount of the aromatic dicarboxylic acid (a-1) is preferably 60-100 mol%, more preferably 80-100 mol%, further preferably 90-100 mol%, and most preferably 95-100 mol%, based on the total moles of the dicarboxylic acid units constituting the semicrystalline semiaromatic polyamide; the amount of the other dicarboxylic acid (a-2) is preferably 0-40 mol%, more preferably 0-20 mol%, further preferably 0-10 mol%, and most preferably equal to or less than 5 mol%, based on the total moles of the dicarboxylic acid units constituting the semicrystalline semiaromatic polyamide;
[0064] The diamine unit is derived from an aliphatic diamine (b-1) or a combination of an aliphatic diamine (b-1) and an aromatic diamine (b-2). The amount of the aliphatic diamine (b-1) is preferably 80-100 mol%, more preferably 90-100 mol%, most preferably 95-100 mol%, based on the total moles of the diamines constituting the semicrystalline semiaromatic polyamide; the amount of the aromatic diamine (b-2) is preferably 0-20 mol%, more preferably 0-10 mol%, most preferably 0-5 mol%, based on the total moles of the diamine units constituting the semicrystalline semiaromatic polyamide.
[0065] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide comprises dicarboxylic acid units and diamine units, the dicarboxylic acid units being derived from an aromatic dicarboxylic acid (a-1) and 0-10 mol %, more preferably 0-5 mol %, of the other dicarboxylic acid (a-2),
[0066] wherein the aromatic dicarboxylic acid (a-1) comprises 10-40 mol%, more preferably 15-30 mol%, most preferably 20-30 mol% of isophthalic acid and 60-90 mol%, more preferably 70-85 mol%, most preferably 70-80 mol% of at least one aromatic dicarboxylic acid selected from the group consisting of terephthalic acid, naphthalene dicarboxylic acid and biphenyl dicarboxylic acid, preferably terephthalic acid or a combination of terephthalic acid and naphthalene dicarboxylic acid; the other dicarboxylic acid (a-2) is an aliphatic dicarboxylic acid and / or an alicyclic dicarboxylic acid; the molar percentage is based on the total moles of the dicarboxylic acid units constituting the semi-crystalline semiaromatic polyamide;
[0067] The diamine units are derived from aliphatic diamine (b-1), or a combination of aliphatic diamine (b-1) and aromatic diamine (b-2). The amount of aliphatic diamine (b-1) is preferably 90-100 mol%, more preferably 95-100 mol%, based on the total moles of diamine units constituting the semicrystalline semiaromatic polyamide; the amount of aromatic diamine (b-2) is preferably 0-10 mol%, more preferably 0-5 mol%.
[0068] In a more preferred embodiment, the aliphatic dicarboxylic acid (a-3) of the other dicarboxylic acids (a-2) is preferably glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecanoic acid, hexadecanedioic acid and octadecanedioic acid, more preferably glutaric acid, adipic acid, sebacic acid and / or dodecanedioic acid.
[0069] In a more preferred embodiment, the aliphatic diamine (b-1) is a linear aliphatic diamine (b-1a) or a combination of a linear aliphatic diamine and a branched aliphatic diamine (b-1b). The linear aliphatic diamine (b-1a) is preferably selected from the group consisting of 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine and 1,12-dodecanediamine. The branched aliphatic diamine (b-1b) is preferably selected from the group consisting of 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2-methyl-1,8-octanediamine, 2,4,4-trimethylhexamethylenediamine and 2,2,4-trimethylhexamethylenediamine.
[0070] Examples of semicrystalline semiaromatic polyamides are polyamide MXD5, polyamide PXD5, polyamide MXD6, polyamide PXD6, polyamide MXD9, polyamide PXD9, polyamide MXD10 and / or polyamide PXD10.
[0071] The polyamide in the present invention may include a polyamide copolymer or a blend of two or more polyamides and their copolymers.
[0072] Semi-crystalline semi-aromatic polyamides are suitably represented by the following symbols,
[0073] -R represents one or more of a linear aliphatic diamine and a branched aliphatic diamine,
[0074] -T represents terephthalic acid,
[0075] -I represents isophthalic acid,
[0076] -A represents one or more aromatic diamines,
[0077] -Y represents one or more of aliphatic dicarboxylic acids,
[0078] -V represents one or more of the lactams.
[0079] Suitable semi-crystalline semi-aromatic polyamides may be represented by PA RT, PA RT / RI, PA RT / BT, PA RT / BT / RI / BI, which include:
[0080] - 60-100 mol% of (T), 0-40 mol% of (I), preferably 60-85 mol% of (T), 15-40 mol% of (I), more preferably 65-80 mol% of (T), 20-35 mol% of (I); based on the total moles of (T) + (I); and
[0081] 100 mol% of (R), R is preferably a linear or branched aliphatic polyamide having 4 to 36 carbon numbers, more preferably 5 to 18 carbon numbers, most preferably 6 to 12 carbon numbers. Examples of these polyamides include PA 4T / 4I, PA 4T / 6I, PA5T, PA 5T / 5I, PA 6T, PA 6T / 6I, PA 6T / 8T, PA 6T / 10T, PA 6T / 10I, PA 9T, PA 10T, PA12T, PA 10T / 10I, PA 6T / 9T, PA 6T / 12T, PA 4T / 6T / DT, PA 4T / 10T / DT, PA 4T / 4I / 6T / 6I / DT / DI, PA6T / 12T / 6I / 12I, PA 6T / 10T / 6I, PA 4T / 6T / 4I / 6I, PA 5T / 6T / 5I / 6I, PA 5T / 4T / 5I / 4I, PA 4T / 10T / 5I / 10I, PA PA 4T / 6T / DT, PA 4T / 10T / DT or PA4T / 4I / 6T / 6I / DT / DI, preferably PA5T, PA6T, PA9T, PA10T, PA 6T / 6I, PA 6T / 10T, PA6T / 12T, PA 6T / 10T / 6I, PA 6T / DT or PA 6T / DT / 6I / DI. Herein, D is 2-methylpentamethylenediamine or 3-methyl-1,5-pentanediamine, or a mixture thereof, and the amount of D is 0-20 mol%, preferably 0-10 mol%, based on the total moles of (R).
[0082] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide is PA 6T / 6I, which contains 65-80 mol% of (T), 20-35 mol% of (I).
[0083] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide is PA 6T / 10T, which contains 10-60 mol% (6T), 40-90 mol% (10T), preferably 10-40 mol% (6T), 60-90 mol% (10T).
[0084] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide is PA 6T / 10T / 6I, which contains 60-90 mol% of (6T), 5-40 mol% of (6I) and 5-45 mol% of (10T).
[0085] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide is PA 6T / 10T / 6, which contains 60-85 mol% of (6T), 15-40 mol% of (10T) and 5-15 mol% of caprolactam.
[0086] Suitable semi-crystalline semi-aromatic polyamides may be represented by PA RT / RY, PA RT / V, PA RT / RI / RY or PA RT / RI / V, which comprise:
[0087] 60-100 mol% of (T), 0-40 mol% of (I); 0-10 mol% of (V), preferably 0-5 mol% of (V); 0-80 mol% of (Y), preferably 0-60 mol% of (Y), more preferably 0-40 mol% of (Y); based on the total moles of (T)+(I)+(V)+(Y); R is preferably a linear aliphatic polyamide having 4 to 36 carbon atoms, more preferably 5 to 18 carbon atoms, and most preferably 6 to 12 carbon atoms. Examples of these polyamides include PA 5T, PA 5T / 5I, PA 5T / 6T / 5I / 6I, PA 5T / 4T / 5I / 4I, PA 4T / 10T / 5I / 10I, PA 5T / 510, PA 6T, PA 6T / 6, PA6T / 12, PA 6T / 6I / 6, PA 6T / 66, PA4T / 410, PA 6T / 610, PA 6T / 612, PA 6T / 1012, PA 9T, PA 9T / 612, PA 9T / 1012, PA 10T, PA 10T / 106, PA 10T / 612, PA 10T / 1012, PA 6T / 6I / 66, PA 10T / 12, PA 10T / 11, PA 11T, PA 12T and PA6T / 6I / 12, preferably PA 6T / 6, PA 66 / 6T, PA 6T / 610 or PA 6T / 612.
[0088] In a preferred embodiment, PA RT / RY comprises 60-100 mol % of (T), 0-40 mol % of (Y), R is 1,6-hexanediamine, 1,9-nonanediamine, 1,10-decanediamine, and Y is dodecanedioic acid.
[0089] The semicrystalline semiaromatic polyamide in the present invention has a melting temperature (Tm) of 250° C. to 350° C., preferably 280° C. to 320° C., most preferably 305° C. to 315° C. The melting temperature is defined as the temperature corresponding to the endothermic peak in the differential scanning calorimetry (DSC) curve obtained by DSC at a heating rate of 10 K / min according to ISO 11357.
[0090] The semicrystalline semiaromatic polyamide in the present invention preferably has a viscosity number of 60-150 ml / g, more preferably 110-130 ml / g, measured in a 0.5 wt% solution in 96 wt% sulfuric acid according to the ISO 307-2007 method.
[0091] In a preferred embodiment, the semi-crystalline semi-aromatic polyamide is selected from the group consisting of polyamide MXD6, polyamide 12T, polyamide 11T, polyamide 10T, polyamide 9T, polyamide 6T, polyamide 6T / 66, polyamide 6T / DT, polyamide 66 / 6T / 61, polyamide 66 / 6T, polyamide 6T / 6, polyamide 6T / 6I, polyamide 5T, polyamide 5T / 5I, polyamide 5T / 6T / 5I / 6I, polyamide 5T / 4T / 5I / 4I, polyamide 5T / 510 and mixtures thereof.
[0092] In another preferred embodiment, the semicrystalline semiaromatic polyamide is at least one selected from the group consisting of PA 4T / 410, PA 4T / 4I, PA 4T / 6I, PA 4T / 10T / 5I / 10I, PA 4T / 6T / DT, PA 4T / 10T / DT, PA4T / 4I / 6T / 6I / DT / DI, PA 5T, PA 5T / 5I, PA 5T / 6T / 5I / 6I, PA 5T / 4T / 5I / 4I, PA 5T / 510, PA6T, PA 6T / 6, PA6T / 12, PA 6T / 6I / 6, PA 6T / 6I / 66, PA 6T / 66, PA 6T / 610, PA 6T / 612, PA 6T / 1012, PA 6T / 6I / 12, PA 6T / 8T, PA 6T / 9T, PA 6T / 10T, PA 6T / 10I, PA 6T / 12T, PA 9T, PA 9T / 612, PA 9T / 1012, PA 10T, PA 10T / 106, PA 10T / 612, PA 10T / 1012, PA 10T / 12, PA 10T / 11, PA 11T, PA 12T and their mixtures.
[0093] The semicrystalline semiaromatic polyamide can be produced using a conventionally known method such as a melt polymerization method or a solution polymerization method.
[0094] The amount of the semi-crystalline semi-aromatic polyamide (A) in the present invention is 69% to 89.9% by weight, preferably 70% to 89% by weight, more preferably 72% to 85% by weight, such as 72%, 75%, 76%, 78%, 79%, 80%, 83%, 85% by weight; based on the total percentage by weight of the insulating film. Suitable semi-crystalline semi-aromatic polyamides may be PA9T or copolymers thereof, PA10T or copolymers thereof, PA11T or copolymers thereof, PA12T or copolymers thereof, and mixtures thereof.
[0095] The polyamides disclosed herein should not be limited to those prepared from virgin crude oil monomers, and may be fully or at least partially bio-based or derived from waste streams or recycling activities, i.e., the polyamides used in the present application may be based on renewable materials, secondary raw materials, or recycled raw materials. For example, PA5T, PA6T, PA9T, PA10T, PA11T, and PA12T used in the present application may be prepared or obtained or derived from monomers obtained in conventional re-monomerization processes.
[0096] Preferably, the flame retardant herein comprises a dialkylphosphinate metal salt (B-1), which comprises a phosphinate metal salt having formula (I), a diphosphinate metal salt having formula (II) or / and a mixture thereof;
[0097]
[0098] wherein R1 and R2 are identical or different and are linear or branched C1-C6-alkyl, preferably linear or branched C1-C4-alkyl, more preferably methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl and / or phenyl;
[0099] M or N is Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K, a protonated nitrogen base or a mixture thereof, preferably Mg, Ca, Al, Zn or a mixture thereof; m is an integer from 1 to 4; n is an integer from 1 to 4;
[0100] R3 is a straight or branched C1-C 10 -alkylene, C6-C 10 -Arylene, C7-C 20 -alkylarylene or C7-C 20 - arylalkylene, preferably a straight-chain or branched C1-C4-alkylene or C6-C 10 - arylene, more preferably methylene, ethylene, n-propylene, isopropylene, n-butylene, tert-butylene, n-pentylene, n-octylene, n-dodecylene, phenylene, naphthylene, phenylmethylene, phenylethylene, phenylpropylene or phenylbutylene.
[0101] R4 and R5 are identical or different and are linear or branched C1-C6-alkyl, preferably linear or branched C1-C4 alkyl, more preferably methyl, ethyl or propyl; q is an integer from 1 to 4; p is an integer from 1 to 4; x is an integer from 1 to 4.
[0102] The protonated nitrogen base is preferably a protonated base of ammonia, melamine, triethanolamine, in particular NH4 + .
[0103] The phosphinic acid used for producing the phosphinic acid metal salt having the formula (I) in the present invention is preferably dimethylphosphinic acid, ethylmethylphosphinic acid, diethylphosphinic acid, methyl-n-propylphosphinic acid.
[0104] The diphosphinic acid used to produce the diphosphinate of formula (II) in the present invention is preferably methane-di(methylphosphinic acid), ethane-1,2-di(methylphosphinic acid), hexane-1,6-di(methylphosphinic acid), benzene-1,4-di(methylphosphinic acid), methylphenylphosphinic acid, diphenylphosphinic acid.
[0105] Examples of the phosphinate metal salts of formula (I) include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, and zinc methyl-n-propylphosphinate. Among them, aluminum diethylphosphinate, zinc diethylphosphinate, aluminum dimethylphosphinate, and zinc dimethylphosphinate are more preferred.
[0106] Examples of diphosphine metal salts having formula (II) include calcium methanedi(methylphosphinate), magnesium methanedi(methylphosphinate), aluminum methanedi(methylphosphinate), zinc methanedi(methylphosphinate), calcium benzene-1,4-(dimethylphosphinate), magnesium benzene-1,4-(dimethylphosphinate), aluminum benzene-1,4-(dimethylphosphinate), and zinc benzene-1,4-(dimethylphosphinate).
[0107] The flame retardant may further comprise a flame retardant synergist (B-2). Suitable flame retardant synergists include phosphorus synergists, nitrogen synergists and phosphorus / nitrogen synergists.
[0108] The phosphorus synergist in the present invention can be a metal phosphite, a polyphosphonate, a phosphazene, a polyphosphonate, an organic phosphate and a mixture thereof. The metal phosphite comprises a structural unit having formula (III) or (IV):
[0109]
[0110]
[0111] wherein T is Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K, a protonated nitrogen base or a mixture thereof, preferably Al and / or Zn; r is 1 to 4; w is 1 to 4; z is 1 to 7, preferably 1 to 4.
[0112] Examples of metal phosphites are Al(H2PO3)3, Al2(HPO3)3, Zn(HPO3), Al2(HPO3)3.4H2O and Al(OH)(H2PO3)2.2H2O, preferably Al2(HPO3)3.
[0113] The protonated nitrogen base is preferably a protonated base of ammonia, melamine, triethanolamine, in particular NH4 + .
[0114] Suitable nitrogen synergists may be melamine condensation products such as melem, melam, melon and mixtures thereof.
[0115] Suitable phosphorus / nitrogen synergists may be reaction products of melamine and polyphosphoric acid, condensation products of melamine and polyphosphoric acid, and mixtures thereof, such as dimelamine pyrophosphate, melamine polyphosphate, melem polyphosphate, melem polyphosphate, and mixtures thereof.
[0116] The mass ratio of the dialkylphosphinate metal salt (B-1) to the flame retardant synergist (B-2) is preferably 60:40 to 90:10, more preferably 75:25 to 90:10, for example 85:15, 80:20.
[0117] Suitable flame retardants may be Clariant's OP series.
[0118] The flame retardant synergist can also be a metal oxide, a metal hydroxide, boehmite, hydrotalcite, hydrocalumite, a metal borate such as zinc borate, a metal hydroxystannate such as zinc hydroxystannate. Suitable metal oxides are magnesium oxide, calcium oxide, zinc oxide, manganese oxide, tin oxide, tin oxide hydrate and mixtures thereof. Suitable metal hydroxides are aluminum hydroxide, magnesium hydroxide, calcium hydroxide, zinc hydroxide and manganese hydroxide.
[0119] In a preferred embodiment, the flame retardant (B) is a mixture of a metal dialkylphosphinate salt (B-1) and a metal phosphite salt comprising a structural unit having the formula (III) or (IV).
[0120] In a preferred embodiment, the flame retardant (B) is a mixture of a dialkylphosphinate metal salt (B-1) and a flame retardant synergist (B-2).
[0121] - a dialkylphosphinate metal salt (B-1) selected from the group consisting of aluminum diethylphosphinate, zinc diethylphosphinate, aluminum dimethylphosphinate and zinc dimethylphosphinate, preferably aluminum diethylphosphinate, and
[0122] - the flame retardant synergist is a metal phosphite containing a structural unit having formula (III) or (IV) selected from the group consisting of: Al(H2PO3)3, Al2(HPO3)3, Zn(HPO3), Al2(HPO3)3.4H2O and Al(OH)(H2PO3)2.2H2O, preferably Al2(HPO3),
[0123] The mass ratio of the metal phosphinate (B-1) to the flame retardant synergist (B-2) is 75:25 to 90:10.
[0124] In a preferred embodiment, the flame retardant (B) is a mixture of a dialkylphosphinate metal salt (B-1) and a flame retardant synergist (B-2).
[0125] - the dialkylphosphinate metal salt (B-1) is at least one selected from the group consisting of aluminum diethylphosphinate, zinc diethylphosphinate, aluminum dimethylphosphinate and zinc dimethylphosphinate, preferably aluminum diethylphosphinate, and
[0126] - the flame retardant synergist (B-2) is at least one selected from the group consisting of melamine polyphosphate, melem polyphosphate, melam polyphosphate,
[0127] The mass ratio of the metal phosphinate (B-1) to the flame retardant synergist (B-2) is 75:25 to 90:10.
[0128] The amount of the flame retardant (B) in the present invention is 10 to 25% by weight, preferably 15 to 25% by weight, such as 15%, 20%, 25% by weight, based on the total percentage by weight of the insulating film.
[0129] The acid scavenger in the present invention includes metal stannates, metal hydroxystannates, and higher fatty acid metal salts.
[0130] The term "metal stannate" in this context does not include partially or fully hydrated metal stannates. Examples of metal stannates are zinc stannate, magnesium stannate, calcium stannate, barium stannate, bismuth stannate and mixtures thereof, preferably zinc stannate and bismuth stannate.
[0131] Examples of metal hydroxystannates are zinc hydroxystannate, bismuth hydroxystannate and mixtures thereof.
[0132] Examples of higher fatty acid metal salts are calcium stearate, zinc stearate, magnesium behenate, magnesium stearate, sodium ricinoleate and potassium palmitate, antimony pyrocatechuate and zinc pyrocatechuate and mixtures thereof, preferably zinc stearate, calcium stearate and magnesium stearate.
[0133] The acid scavenger may also be zinc oxide, calcium lactate, hydrotalcite, dihydrotalcite and mixtures thereof.
[0134] In a preferred embodiment of the present invention, the acid scavenger is a metal stannate, preferably anhydrous zinc stannate and / or anhydrous bismuth stannate.
[0135] The amount of the acid scavenger (C) in the present invention is 0.1 to 1% by weight, preferably 0.1 to 0.5% by weight, based on the total percentage by weight of the insulating film.
[0136] These additional additives in the present invention can be selected from conventional additives for plastics, such as lubricants, antioxidants, release agents, impact modifiers, heat stabilizers, light stabilizers such as UV stabilizers, plasticizers, surfactants, nucleating agents, coupling agents, antimicrobial agents, antistatic agents and any combination thereof.
[0137] For the purpose of the present invention, the additives may be used in conventional amounts. For example, the insulating film may contain at least one additive in an amount of 0.01 to 5% by weight based on the total percentage by weight of the insulating film.
[0138] The insulating film may, for example, contain an antioxidant. Suitable antioxidants are antioxidants based on aromatic amines, antioxidants based on hindered phenols and antioxidants based on phosphites, in particular antioxidants based on hindered phenols. Examples of hindered phenol-based antioxidants include, but are not limited to, α-[3-[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropyl]-ω-[3-[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]-1-oxopropoxy]poly(oxy-1,2-ethanediyl), 2,4-bis[(octylthio)methyl]-o-cresol, octyl-3,5-di-tert-butyl-4-hydroxy-hydrocinnamate, 3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionic acid C7-C9-branched alkyl ester, 2,4-bis[(dodecylthio)methyl]-o-cresol, 4,4'-butylenebis-(3-methyl-6-tert-butylphenol), 3 ,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionic acid octadecyl ester, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), triethylene glycol bis[3-(3-tert-butyl-5-methyl-4-hydroxyphenyl)propionate], 2,4-bis(n-octylthio)-6-(4-hydroxy-3,5-di-tert-butylanilino)-1,3,5-triazine, tris-(3,5-di-tert-butyl-4-hydroxybenzyl) isocyanurate, 2,2-thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], N,N'-1,6-hexanediylbis[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenylpropionamide.
[0139] The amount of the antioxidant (when present) may be 0.01 to 1% by weight, or 0.1 to 0.5% by weight, based on the total percentage by weight of the insulating film.
[0140] The insulating film may, for example, contain a heat stabilizer. Suitable heat stabilizers are organic phosphinates, inorganic hypophosphites, inorganic phosphonates, organic phosphites and mixtures thereof, inorganic phosphonates and organic phosphinates being preferred. Examples of heat stabilizers are sodium phosphonate, potassium phosphonate, sodium phenylphosphonate, potassium phenylphosphonate, lithium phenylphosphonate, sodium ethylphosphonate, potassium ethylphosphonate, ammonium phosphonate, sodium hypophosphite, potassium hypophosphite, lithium hypophosphite, magnesium hypophosphite, calcium hypophosphite and ammonium hypophosphite, sodium hypophosphite, potassium hypophosphite, lithium hypophosphite, magnesium hypophosphite, calcium hypophosphite, ammonium hypophosphite and sodium phenylphosphinate.
[0141] Suitable heat stabilizers are halogen-containing compounds, preferably metal halides, more preferably KCl, KBr, KI and CuI, most preferably a mixture of KI and CuI.
[0142] The insulating film may, for example, contain a lubricant. Suitable lubricants are preferably esters or amides of saturated or unsaturated aliphatic carboxylic acids having 10 to 40, preferably 16 to 22 carbon atoms and saturated aliphatic alcohols or amines having 2 to 40, preferably 2 to 6 carbon atoms. The carboxylic acid may be monobasic or dibasic. Examples of carboxylic acids are nonanoic acid, palmitic acid, lauric acid, heptadecanoic acid, dodecanedioic acid, behenic acid, and particularly preferably stearic acid, capric acid, and also montanic acid (a mixture of fatty acids having 30 to 40 carbon atoms). The aliphatic alcohol may be monobasic to tetrabasic. Examples of aliphatic alcohols are n-butanol, n-octanol, stearyl alcohol, ethylene glycol, propylene glycol, neopentyl glycol and pentaerythritol, preferably glycerol and pentaerythritol. The aliphatic amine may be mono- to trifunctional. Examples of aliphatic amines are stearylamine, ethylenediamine, propylenediamine, hexamethylenediamine and di(6-aminohexyl)amine, particular preference being given here to ethylenediamine and hexamethylenediamine.
[0143] Preferred esters or amides are N,N'-ethylenebis(stearamide), glyceryl distearate, glyceryl tristearate, glyceryl monopalmitate, glyceryl trilaurate, glyceryl monobehenate and pentaerythritol tetrastearate. N,N'-ethylenebis(stearamide) is particularly preferred as a lubricant in the insulating film according to the present invention.
[0144] It is also possible to use mixtures of various esters or amides, or combinations of esters and amides in any desired mixing ratio.
[0145] Other lubricants are preferably long-chain fatty acids (e.g. stearic acid or behenic acid), their salts (e.g. calcium stearate or zinc stearate), or montan wax (a mixture of linear saturated carboxylic acids with a chain length of 28 to 32 carbon atoms), calcium montanate or sodium montanate, and also low molecular weight polyethylene waxes and low molecular weight polypropylene waxes.
[0146] The amount of the lubricant (when present) may be 0.01 to 2% by weight, or 0.2 to 1% by weight, based on the total percentage by weight of the insulating film.
[0147] The insulating film may, for example, contain an impact modifier. Suitable impact modifiers may include polyolefin-based, styrene-based, unsaturated carboxylic acid-based impact modifiers. Suitable impact modifiers may also be those modified by functional blocks such as epoxy-functional blocks and / or anhydride blocks. The epoxy-functional blocks may be units derived from glycidyl (meth)acrylate. The anhydride blocks may be units derived from maleic anhydride.
[0148] Suitable polyolefin-based impact modifiers may include polyolefins comprising repeating units derived from olefins having 2 to 10 carbon atoms. Examples of such olefins include ethylene, 1-butene, 1-propylene, 1-pentene, 1-octene, and mixtures of ethylene and 1-octene, preferably ethylene, 1-propylene, and mixtures of ethylene and 1-octene.
[0149] Suitable unsaturated carboxylic acid-based impact modifiers may include blocks derived from carboxylic acids and their derivatives such as esters, imides and amides. Suitable carboxylic acids and their derivatives are, for example, acrylic acid, acrylic acid, methacrylic acid, maleic acid, fumaric acid, glutaconic acid, itaconic acid, citraconic acid, (meth)acrylates, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate and isobutyl (meth)acrylate.
[0150] The impact modifier can also be a binary or ternary polymer or a core-shell structure polymer. Examples of such impact modifiers include styrene / ethylene / butylene copolymers (SEBS), ethylene-methyl acrylate-glycidyl methacrylate terpolymers, ethylene / propylene / diene rubber (EPDM) and ethylene-octene copolymers.
[0151] The amount of the impact modifier (when present) may be 0.01 to 5% by weight, or 1 to 5% by weight, based on the total percentage by weight of the insulating film.
[0152] The insulating film may, for example, contain a plasticizer including, but not limited to, dioctyl phthalate, dibenzyl phthalate, butyl benzyl phthalate, hydrocarbon oil, and N-(n-butyl)benzenesulfonamide.
[0153] The amount of the plasticizer (when present) may be 0.01 to 5% by weight, or 1 to 5% by weight, based on the total percentage by weight of the insulating film.
[0154] The insulating film may contain, for example, a nucleating agent which does not cause a decrease in physical properties of a molded product when used in a small amount and has a significant crystallization promoting effect as desired.
[0155] The nucleating agent herein may be selected from at least one of an inorganic nucleating agent and an organic nucleating agent having a particle size of less than 1 μm. Preferably, the inorganic nucleating agent is at least one of talc, montmorillonite and calcium carbonate; and the organic nucleating agent is at least one of sodium benzoate, dibenzyl sorbitol and sodium carboxylate.
[0156] The amount of the nucleating agent (when present) may be 0.01 to 5% by weight, or 1 to 5% by weight, based on the total percentage by weight of the insulating film.
[0157] The insulating film in the present invention is a film or a thin sheet, and the thickness can be adjusted based on application requirements, preferably in the range of 50 μm to 600 μm, more preferably in the range of 100 μm to 400 μm, most preferably in the range of 150 μm to 300 μm.
[0158] The insulating film of the present invention exhibits excellent flame retardancy, which is close to V-0UL94 VTM for a sample having a thickness of 0.20 mm and close to V-0UL94 for a sample having a thickness of 0.8 mm.
[0159] For the specimens with thicknesses of 0.75 mm and 1.5 mm, the insulating film in the present invention can pass the GWFI (Glow Wire Flammability Index) test at 960° C. according to DIN EN 60695-2-12.
[0160] For a specimen with a thickness of 0.75 mm, the insulating film of the present invention can pass the GWIT (glow wire ignition temperature) test at 775° C. according to DIN EN 60695-2-13.
[0161] The insulating film of the present invention has a dielectric strength of more than 40 KV / mm, preferably more than 45 KV / mm, measured in Midel 7131 ester liquid according to IEC 60243-1 at room temperature in the conditioned state.
[0162] The insulating film of the present invention has a dielectric strength of more than 70 KV / mm, preferably more than 72 KV / mm, measured in Midel 7131 ester liquid according to IEC 60243-1 at room temperature in the dry state.
[0163] The insulating film in the present invention has a dielectric strength of more than 40 KV / mm, preferably more than 45 KV / mm, measured in Midel 7131 ester liquid according to IEC 60243-1 at 150° C. in the dry state.
[0164] The insulating film of the present invention has a dielectric strength drop of not more than 40%, preferably 35%, at 120°C compared to the dielectric strength at room temperature measured in dry state according to IEC 60243-1 in Midel 7131 ester liquid.
[0165] The insulating film of the present invention has a dielectric strength drop of not more than 45%, preferably 37%, at 150°C compared to the dielectric strength at room temperature measured in dry state according to IEC 60243-1 in Midel 7131 ester liquid.
[0166] The surface of the insulating film in the present invention is flat, smooth, uniform and has no defects such as fish eyes, burrs, cracks, etc.
[0167] Therefore, the present invention provides a coil bobbin comprising the insulating film of the present invention.
[0168] In addition, the present invention provides the use of the insulating film, which can be used in the following fields: packaging; electrical insulating materials for motors, transformers, cables, etc.; dielectric materials for capacitor applications, etc.; magnetic tape materials, such as cassette tapes, data storage tapes for digital data storage, and video tapes; protective sheets for solar cell substrates, liquid crystal panels, display devices, etc.; electronic substrate materials, such as LED mounting substrates, substrates for flexible printed wiring, flexible flat cables, etc.; heat-resistant belts, such as covering films, heat-resistant masking tapes and industrial processing tapes for flexible printed wiring; heat-resistant bar code labels; heat-resistant reflectors; insulating tapes; various release films; heat-resistant base films; films; molding materials; agricultural materials; medical materials; civil engineering and construction materials; filter membranes, etc., household membranes, industrial materials.
[0169] Therefore, the present invention provides a manufacturing method for producing the insulating film of the present invention, which comprises (S1) heating particles prepared from a polyamide-based composition having the same components as the insulating film and melt-extruding through a slit die to form an extruded layer, and cooling the extruded layer to obtain an insulating film or an unstretched film.
[0170] In a preferred embodiment of the present invention, the manufacturing method includes (S2) stretching the unstretched film into an insulating film.
[0171] In a preferred embodiment of the present invention, the manufacturing method includes (S3) thermal fixing and cooling to obtain the insulating film.
[0172] In a more preferred embodiment of the present invention, the manufacturing method comprises:
[0173] (S1) heating and melt-extruding pellets prepared from a polyamide-based composition having the same components as the insulating film through a slit die to form an extruded layer, and cooling the extruded layer to obtain an insulating film or an unstretched film, and
[0174] (S2) The unstretched film is stretched into an insulating film.
[0175] In a more preferred embodiment of the present invention, the manufacturing method comprises:
[0176] (S1) heating pellets prepared from a polyamide-based composition having the same components as the insulating film and melt-extruding through a slit die to form an extruded layer, and cooling the extruded layer to obtain an insulating film or an unstretched film,
[0177] (S2) stretching the unstretched film, and
[0178] (S3) Thermal fixing and cooling to obtain an insulating film.
[0179] These particles are prepared according to conventional methods. For example, the individual components of the insulating film according to the present invention can be mixed and then molded, for example, via injection and / or extrusion in conventional mixing equipment such as a screw extruder, Brabender mixer or Banbury mixer to form an article. The mixing or extrusion temperature used herein is generally 280° C. to 330° C.
[0180] Regarding step (S1), it is preferred that the particles are melted at a temperature of 280°C to 340°C and then screw extruded into a layer or film having a thickness of 50-600 μm. The rotation speed of the screw is not limited in the present invention, for example, 30 to 80 rpm. Cooling roller: 100°C-180°C. Cooling can be achieved via conventional methods, for example, via a cooling roller. The cooling roller temperature is preferably 110°C to 170°C.
[0181] The stretching in step (S2) can be performed by a conventional method.
[0182] In a preferred embodiment of the present invention, during the process of step (S2), the unstretched film is stretched 0 to 3 times in the longitudinal direction, more preferably 0.1 to 1.5 times in the longitudinal direction.
[0183] In a preferred embodiment of the present invention, the unstretched film is stretched at a temperature of 125°C to 180°C.
[0184] In a preferred embodiment of the present invention, after the insulating film is obtained, it is preferably pulled out from a roll at a speed of 1 m / min to 15 m / min, more preferably 2 m / min to 8 m / min.
[0185] Examples
[0186] Various aspects of the present invention are more fully illustrated by the following examples, which are presented for the purpose of illustrating certain aspects of the present invention and should not be construed as limiting thereof.
[0187] The following materials and test methods were used in the examples.
[0188] Material:
[0189] Table 1 Materials used in the examples
[0190]
[0191] General procedure for preparing test specimens
[0192] Preparation of particles:
[0193] The naturally colored polyamide 9T is dried at 120°C to a moisture content of less than 0.1% by weight, and all other components (C) to (D) are premixed in a drum mixer for 10 minutes. In the next step, the dried polyamide 9T is melt-extruded together with the dried blending components using a twin-screw extruder with a diameter of 26 mm and an L / D ratio of 44. The flame retardant (B) is added to the polymer melt via a side feeder. The extruder is operated at a rotation speed of 350 rpm, a throughput of 30 kg / h, and a barrel temperature of 280°C to 330°C (using a flat temperature curve). The obtained strand is cooled in a water bath and granulated.
[0194] Preparation of insulating film:
[0195] The obtained pellets were heated and melt-extruded through a slit die via a single screw extruder (rotation speed: 50 rpm, flat temperature profile: 340° C., cooling roll: 140° C., pull-out speed: 4.8 m / min) to produce a film having a thickness of 240 μm.
[0196] Measurement:
[0197] The test specimens for testing listed in Table 2 were injection molded in an Arburg 420C injection molding machine at a melt temperature of about 340°C and a mold temperature of about 80°C.
[0198] 1. The tensile modulus, tensile strength and elongation at break of a specimen having a thickness of 4 mm were measured according to ISO 527-2-1993. Type 1 test specimens described in ISO 527-2-1993 were used. Charpy notched impact strength and Charpy unnotched impact strength were measured according to ISO 179-2 / 1eA. All test specimens were conditioned at 23° C. and 50% relative humidity for 24 h. The test was carried out under the same environment as the conditioning.
[0199] 2. The melt volume flow rate (MVR) was tested according to ISO 1133 at 325°C and 5 kg load.
[0200] 3. Viscosity numbers were determined according to ISO 307 at 25°C as a 0.5 wt% solution in 96 wt% sulfuric acid.
[0201] 4. Flame retardancy was determined by the UL 94V method (Underwriters Laboratories Inc. Standard of Safety, "Test for Flammability of Plastic Materials for Parts in Devices and Appliances", pp. 14-18, Northbrook 1998).
[0202] 5. The Glow Wire Flammability Index (GWFI) is tested on the test specimens according to DIN EN 60695-2-12. The GWFI test is a general suitability test for plastics in contact with potential-carrying parts. The temperature determined is the highest temperature at which one of the following conditions is met in three consecutive tests: (a) the specimen does not ignite or (b) the afterflame time or afterglow time after exposure to the glow wire is 30 seconds and the substrate does not ignite.
[0203] 6. Glow-wire ignition temperature (GWIT) is tested on specimen plates according to DIN EN 60695-2-13. In the GWIT test, the maximum temperature is determined for 3 test specimens (e.g. on plates with a geometry of 60×60×1.5 mm) using a glow wire at a temperature between 650° C. and 960° C. and an exposure time of the glow wire that does not lead to ignition. The specified glow-wire ignition temperature is 25 K above the determined maximum temperature. The ignition criterion is a flame with a burning time of >5 seconds.
[0204] 7. Volume resistivity was measured according to IEC 62631-3-1.8. Dielectric strength was measured in Midel 7131 ester fluid according to IEC60243-1. Midel 7131 is a biodegradable synthetic ester dielectric fluid designed to provide a replacement for mineral oil, silicone fluids and dry-type transformers. Ball / ball electrodes with 20 mm diameter. Voltage Slew Rate = 2.0 kV / s.
[0205] Table 2
[0206] Components / Test Methods Example 1 A 78.7% B 19.85% C 0.15% D / 1 0.6% D / 2 0.35% D / 3 0.12% D / 4 0.03% D / 5 0.2% VN / [ml / g] 122 MVR 325 / 5 / [ccm / 10min] 45 Tensile modulus / [MPa] 3200 Tensile strength / [MPa] 62 Elongation at break / [%] 4.3 <![CDATA[Charpy V-notch impact energy / kJ / m 2 > 44 <![CDATA[Charpy V-notch at -30 °C / kJ / m 2 > 52 <![CDATA[Charpy V-notch / kJ / m 2 > 3.0 UL94VTM(0.2mm) V-0 UL94(0.8mm) V-0 GWFI 960℃ / 0.75mm pass GWIT 775℃ / 0.75mm pass GWFI 960℃ / 1.5mm pass
[0207] Table 3 Membrane properties
[0208]
[0209]
[0210] "Comp.": comparison; "Ex.": example; "*" measured at room temperature (i.e., 23°C) under conditioned conditions; " # " is measured at room temperature (i.e., 23°C) in a dry state (i.e., the dry state is achieved by keeping the sample at 100°C under vacuum for 24 hours). The T410 film presented as Comp.1 in Table 3 above is purchased from DuPont 410.
[0211] As can be seen from the results in Table 3, the insulating film of Ex. 1 (i.e., N4U41 film) prepared by the polyamide-based composition according to the present invention shows significantly increased dielectric strength as well as relatively low thickness and excellent flame retardancy compared to the Comp. 1T410 film. Considering that the cost of the Comp. 1T410 film is generally much higher than that of the Ex. 1N4U41 film, the present invention provides an effective way to obtain an insulating film having excellent dielectric strength, high volume resistivity, and outstanding flame retardancy.
[0212] Table 4 Dielectric strength properties of PA9T insulation film of Example 1
[0213]
[0214] “ # "Measured in a dry state (ie, the dry state is achieved by keeping the sample at 100°C under a vacuum environment for 24 hours).
[0215] Surprisingly, it can be seen from the results in Table 4 that the insulating film prepared by the polyamide-based composition according to the present invention even shows a relatively high dielectric strength (i.e., 46 kV / mm) at a high temperature of 150° C., and the dielectric strength at 150° C. is reduced by only about 37% compared to the dielectric strength at room temperature (i.e., 23° C.) measured in a dry state in Midel 7131 ester liquid according to IEC 60243-1. In addition, the dielectric strength of the insulating film at 120° C. can still be maintained above 45 (i.e., 48), which is about 34% lower than the dielectric strength at room temperature (i.e., 23° C.) measured in a dry state. Therefore, the insulating film provided by the present invention exhibits a relatively low dielectric strength reduction in response to temperature increase, and thus shows excellent dielectric strength stability when subjected to significantly increased temperatures.
[0216] Table 5 Volume resistivity properties of PA9T insulating film of Example 1
[0217]
[0218] Also surprisingly, it can be seen from the results in Table 5 that the insulating film prepared from the polyamide-based composition according to the present invention shows a high volume resistivity at room temperature. Even at a high temperature of 150°C, the volume resistivity can still be maintained at 3.1E+09Ω*cm, thus proving that the insulating film still has improved electrical insulation properties at high temperatures.
[0219] Table 6
[0220] Components Example 2 Example 3 A 69% 72% B 25% 23% C 1.0% 0.4% D / 1 1.2% 2.4% D / 2 0.8% 0.2% D / 3 0.3% 0.8% D / 4 1.7% 1.2% D / 5 1.0% 0
[0221] The insulating films produced by the above polyamide-based composition examples provided in Table 6 show excellent flame retardancy, a specimen with a thickness of 0.2 mm can approach V-0UL94 VTM, a specimen with a thickness of 0.8 mm can approach V-0UL94, and a specimen with a thickness of 0.4 mm can approach V-2UL94, and specimens with a thickness of 0.75 mm and 1.5 mm can also pass the GWFI (Glow Wire Flammability Index) test at 960° C. according to DIN EN 60695-2-12.
[0222] Regarding insulation properties, the insulating films produced by Examples 2-3 had an excellent dielectric strength of over 40 KV / mm at room temperature, and also exhibited excellent dielectric strength stability, wherein the dielectric strength at 150°C decreased by no more than 45% compared to the dielectric strength at room temperature measured in a dry state in Midel 7131 ester liquid according to IEC 60243-1.
[0223] In addition, the mechanical properties of the above insulating film prepared from the polyamide-based composition according to the present invention can meet the requirements for applications in various technical fields, especially in electrical and electronic systems, new energy vehicles, electrical insulation materials for motors (which include coil skeletons of insulating films), packaging and heat-resistant materials.
[0224] It will be apparent to those skilled in the art that various modifications and variations may be made in the present invention without departing from the scope or spirit of the present invention. It is intended that the embodiments and examples be considered illustrative only. Therefore, the present invention is intended to cover such modifications and variations within the scope of the appended claims and their equivalents.
Claims
1. An insulating film prepared by a polyamide-based composition, the polyamide-based composition comprising: A) 69 to 89.9% by weight of polyamide, B) 10 to 25% by weight of a flame retardant, C) 0.1 to 1.0% by weight of an acid scavenger, D) 0 to 5% by weight of further additives, The total percentage by weight of components A) to D) is 100%.
2. The insulating film according to claim 1, wherein The polyamide comprises at least one semicrystalline semiaromatic polyamide comprising dicarboxylic acid units, diamine units and optionally units derived from other monomers such as amino acid and / or lactam units, and the dicarboxylic acid units or diamine units have aromatic groups.
3. The insulating film according to claim 2, wherein The semicrystalline semiaromatic polyamide comprises aromatic dicarboxylic acid units and aliphatic diamine units, or aliphatic and / or alicyclic dicarboxylic acid units and aromatic diamine units.
4. The insulating film according to any one of claims 1 to 3, wherein The semicrystalline semiaromatic polyamide is at least one selected from the group consisting of PA 4T / 410, PA 4T / 4I, PA 4T / 6I, PA 4T / 10T / 5I / 10I, PA 4T / 6T / DT, PA 4T / 10T / DT, PA 4T / 4I / 6T / 6I / DT / DI, PA 5T, PA 5T / 5I, PA 5T / 6T / 5I / 6I, PA 5T / 4T / 5I / 4I, PA 5T / 510, PA 6T, PA 6T / 6, PA6T / 12, PA 6T / 6I / 6, PA 6T / 6I / 66, PA 6T / 66, PA 6T / 610, PA 6T / 612, PA 6T / 1012, PA 6T / 6I / 12, PA 6T / 8T, PA PA 6T / 9T, PA 6T / 10T, PA 6T / 10I, PA6T / 12T, PA 9T, PA 9T / 612, PA 9T / 1012, PA 10T, PA 10T / 106, PA 10T / 612, PA 10T / 1012, PA10T / 12, PA 10T / 11, PA 11T, PA 12T or any combination thereof.
5. The insulating film according to any one of claims 1 to 4, wherein The flame retardant includes a dialkylphosphinate metal salt (B-1), which includes a phosphinate metal salt having formula (I), a diphosphinate metal salt having formula (II), or a mixture thereof; wherein R1 and R2 are identical or different and are linear or branched C1-C6-alkyl, preferably linear or branched C1-C4-alkyl, more preferably methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, n-pentyl and / or phenyl; wherein M or N is Mg, Ca, Al, Sb, Sn, Ge, Ti, Zn, Fe, Zr, Ce, Bi, Sr, Mn, Li, Na, K, a protonated nitrogen base or a mixture thereof, preferably Mg, Ca, Al, Zn or a mixture thereof; m is an integer from 1 to 4; n is an integer from 1 to 4; Where R3 is a straight or branched C1-C 10 -alkylene, C6-C 10 -Arylene, C7-C 20 -alkylarylene or C7-C 20 - arylalkylene, preferably a straight-chain or branched C1-C4-alkylene or C6-C 10 - arylene, more preferably methylene, ethylene, n-propylene, isopropylene, n-butylene, tert-butylene, n-pentylene, n-octylene, n-dodecylene, phenylene, naphthylene, phenylmethylene, phenylethylene, phenylpropylene or phenylbutylene; wherein R4 and R5 are identical or different and are linear or branched C1-C6-alkyl, preferably linear or branched C1-C4 alkyl, more preferably methyl, ethyl or propyl; q is an integer from 1 to 4; p is an integer from 1 to 4; x is an integer from 1 to 4.
6. The insulating film according to claim 5, wherein The flame retardant further includes a flame retardant synergist (B-2), which is at least one selected from the group consisting of a phosphorus synergist, a nitrogen synergist and / or a phosphorus / nitrogen synergist.
7. The insulating film according to any one of claims 1 to 6, wherein The acid scavenger includes at least one selected from the group consisting of metal stannates, metal hydroxystannates, higher fatty acid metal salts, or any combination thereof.
8. The insulating film according to any one of claims 1 to 7, wherein These additional additives may be at least one selected from the group consisting of lubricants, antioxidants, mold release agents, impact modifiers, heat stabilizers, light stabilizers, plasticizers, surfactants, nucleating agents, coupling agents, antimicrobial agents, antistatic agents, and any combination thereof.
9. The insulating film according to any one of claims 1 to 8, wherein The film has a thickness in the range of 50 μm to 600 μm, more preferably in the range of 100 μm to 400 μm, most preferably in the range of 150 μm to 300 μm.
10. The insulating film according to any one of claims 1 to 9, wherein The film has a dielectric strength of more than 40 KV / mm measured in Midel 7131 ester liquid according to IEC 60243-1 at room temperature in the conditioned state.
11. The insulating film according to any one of claims 1 to 9, wherein The film has a dielectric strength of over 70 KV / mm measured in Midel 7131 ester liquid according to IEC 60243-1 at room temperature in the dry state.
12. The insulating film according to any one of claims 1 to 9, wherein The film has a dielectric strength of over 40 KV / mm measured in Midel 7131 ester liquid according to IEC 60243-1 at 150°C in the dry state.
13. The insulating film according to any one of claims 1 to 12, wherein The film has a dielectric strength drop of no more than 45% at 150°C compared to the dielectric strength at room temperature measured in the dry state according to IEC 60243-1 in Midel 7131 ester liquid.
14. Use of a polyamide-based composition in the preparation of an insulating film, wherein the insulating film comprises: A) 69 to 89.9% by weight of polyamide, B) 10 to 25% by weight of a flame retardant, C) 0.1 to 1.0% by weight of an acid scavenger, D) 0 to 5% by weight of further additives, The total percentage by weight of components A) to D) is 100%.
15. The use according to claim 12, wherein Pellets prepared from a polyamide-based composition having the same components as the insulating film are extruded, and cooled to obtain an insulating film or an unstretched film.
16. The use according to any one of claims 13, wherein The unstretched film is stretched into an insulating film.
17. The use according to any one of claims 13 to 14, wherein The unstretched film is stretched, and heat-set and cooled to obtain an insulating film.
18. The use according to any one of claims 13 to 15, wherein These granules are preferably melted at a temperature of 280° C. to 340° C. and then screw extruded into a film having a thickness of 50-600 μm.
19. Use of the insulating film according to any one of claims 1 to 11 for producing components in electrical and electronic systems, new energy vehicles and electrical insulating parts for motors.
Citation Information
Patent Citations
Polyamide and polyamide film comprising the same
JP2000186141A
Bobbin for motor
JP2008263704A
Semi-aromatic polyamide sheet and method for producing the same
JP2018135414A
Motor bobbin and method for manufacturing same
WO2015033696A1